RETRACTED AND REPLACED: Strategic pathways to International Classification of Diseases, 11th Revision adoption in France and the United States - Bastien Boussat; Robert Jakob; Laurent Boyer; Patrick S Romano (Health Affairs Scholar, 2025)
Abstract This article has been retracted and replaced. Please see https://doi.org/10.1093/haschl/qxaf098 for details. The replacement article can be found at https://doi.org/10.1093/haschl/qxaf099.